Alagille Syndrome: Resolution of Xanthomas - NJ Leonard; V Dias; HG Parsons (Canadian Journal of Gastroenterology)
Alagille syndrome is a rare autosomal dominant disorder characterized by chronic cholestasis due to paucity of intrahepatic biliary ducts, characteristic facies, peripheral pulmonary stenosis, ocular posterior embryotoxon and skeletal abnormalities. Very little information is available on the cholestatic, lipid and lipoprotein profiles in individuals with Alagille syndrome. The course of xanthomatosis and the lipid-lipoprotein profile of a 15-year-old male with incomplete Alagille syndrome with marked xanthomatosis and extremely elevated cholesterols secondary to cholestasis is reported. He showed gradual resolution of xanthomas beginning at age 12 years with a concurrent reduction in his total serum cholesterol. The lipid studies showed that the majority of cholesterol was found in low density lipoprotein (LDL) with lesser amounts in lipoprotein (Lp)-X, a lipoprotein precursor complex seen in patients with cholestasis, and high density lipoprotein (HDL). With resolution of xanthomas, LDL and Lp-X decreased while HDL-cholesterol and apolipoprotein (Apo) A-I increased. Gamma glutamyltransferase and bilirubin decreased but remained 15- and threefold elevated, respectively.